Developing a Brand Image Using Giveaway Merchandise: Survey of Official Oreo Instagram Followers - Prida Ariani Ambar Astuti (Jurnal Visi Komunikasi, 2026)
The success of a company's marketing strategy depends mainly on its brand image. Consumers rely on the brand image to evaluate products or brands. The more favorable the brand image, the more interested and attentive consumers will be towards the product or brand. Oreo is one such brand that partnered with the Korean girl group Blackpink to share giveaway merchandise content on their official Instagram account @oreo_indonesia. A quantitative survey was conducted among Instagram followers of @oreo_indonesia, which revealed a positive and robust impact between the giveaway content and Oreo's brand image. The visual cues in the content significantly influenced brand image, as respondents were already familiar with Oreo's strengths, advantages, and uniqueness. Additionally, the language used in the content piqued the audience's interest in the collaboration and the Oreo brand. Therefore, the research findings demonstrate that Oreo can create a compelling message that motivates consumers to participate in the Blackpink Merchandise Giveaway program. Keywords: brand image, giveaway, merchandise, oreo, Blackpink